1992
DOI: 10.1007/bf00376432
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sex hormone binding globulin, high density lipoprotein cholesterol and plasma lipids in male cyclists during training and competition

Abstract: This study was performed on 13 professional race-cyclists to examine changes in sex hormone binding globulin (SHBG), high density lipoprotein cholesterol (HDL-C) and serum lipid concentrations after training and after competition. While SHBG, total cholesterol and phospholipids increased and free fatty acids (FFA) decreased significantly during training, HDL-C and FFA increased and SHBG and triglycerides (TG) decreased significantly during the competition period. These latter changes in serum lipids and lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The results of this study are consistent with our findings. The mechanisms responsible for the increase in serum testosterone levels during exercise are controversial, and may include decreased testosterone clearance, hemoconcentration, increased SHBG, catecholamine, precursor molecule DHEA sulfate, and testosterone production due to stimulation by factors other than LH and the slight decrease in progesterone [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study are consistent with our findings. The mechanisms responsible for the increase in serum testosterone levels during exercise are controversial, and may include decreased testosterone clearance, hemoconcentration, increased SHBG, catecholamine, precursor molecule DHEA sulfate, and testosterone production due to stimulation by factors other than LH and the slight decrease in progesterone [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 98%
“…First, high levels of bioavailable testosterone has been associated with increased risk of prostate cancer (Gann et al, 1996;. Several studies have reported lower levels of free testosterone (Tikkanen et al, 1998;Tymchuk et al, 2001) in athletically trained men relative to untrained men and immediately after exercise (Nindl et al, 2001) as well as increased levels of sex hormone binding globuline (SHBG) immediately after exercise in older men (Zmuda et al, 1996) and after an exercise programme (Caballero et al, 1992;Tymchuk et al, 1998). However, there are also studies showing increasing levels of testosterone with increasing levels of exercise (Zmuda et al, 1996).…”
Section: Epidemiologymentioning
confidence: 99%
“…Some evidence indicates a role for aerobic physical activity in SHBG production, at least in men. SHBG concentrations have been observed to increase acutely with such exercises as cycle ergometry, and with longer-term endurance training (38)(39)(40)(41), although some reports involving endurance-trained younger men have not confirmed this effect (18,21,37,42). As SHBG concentrations vary inversely with circulating insulin (43), a plausible explanation for greater SHBG values in trained older men could be attenuation of agerelated insulin-resistance.…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 99%